NILAI ANAK DALAM KELUARGA (STUDI KASUS ANAK TUNAGRAHITA DI DESA RAMBAH HILIR TENGAH) - Norma Yulita; Mita Rosaliza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research was doing at Rambah Hilir Tengah village at Rambah Hilir Subdistrict, The aim of this research is to know about value of child in Family (case study is mentally disabled child in special education school at Rambah Hilir Tengah village. Focuss topic at this research is the value of child, that is economic value and social value in mentally disabled’s family. The writer used kuantitative method and used purposive sampling technik, data instrument is observation, interview, questionnaire, and documentation. This research is talk about mentally disabled child have advantages and deficiency that any in family at Rambah Hilir Tengah village, so that value of child in mentally disabled’s family is a value that must accounted every value of child in mentally disabled’s family have a characteristic and every value that any in mentally disabled’s family, so that the Researcher got a answer that value of child like ekconomi value and social value in mentally disbaled’s family Rambah Hilir Tengah Village, so that value can be applied and be accepted in family’s institute. In economic value that any at mentally disabled’s child’s family consider in education facet, because with economic that make parents consider to give a good education to their child. Cause in the education is very important to make a better future to every child, that for mentally disabled’s child or normally child, so for that child can get education and can study at school with cause of economic factor, that in mentally disabled child’s family that have capable or haven’t capable, so that with Economic value that in mentally disabled family have load or not with condition, and with social value in this mentally disabled family Rambah Hilir Tengah Village will consider that social value will be faced every family members in receive mentally disabled child that have defiency and adventages of each, and happieness that feel of every family members in mentally disabled child’s family at Rambah Hilir Tengah Village. Keyword’s :value of child, economic value, social value